5(4x-5)+3(18-5x)=2(2x+3)-2

Simple and best practice solution for 5(4x-5)+3(18-5x)=2(2x+3)-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(4x-5)+3(18-5x)=2(2x+3)-2 equation:


Simplifying
5(4x + -5) + 3(18 + -5x) = 2(2x + 3) + -2

Reorder the terms:
5(-5 + 4x) + 3(18 + -5x) = 2(2x + 3) + -2
(-5 * 5 + 4x * 5) + 3(18 + -5x) = 2(2x + 3) + -2
(-25 + 20x) + 3(18 + -5x) = 2(2x + 3) + -2
-25 + 20x + (18 * 3 + -5x * 3) = 2(2x + 3) + -2
-25 + 20x + (54 + -15x) = 2(2x + 3) + -2

Reorder the terms:
-25 + 54 + 20x + -15x = 2(2x + 3) + -2

Combine like terms: -25 + 54 = 29
29 + 20x + -15x = 2(2x + 3) + -2

Combine like terms: 20x + -15x = 5x
29 + 5x = 2(2x + 3) + -2

Reorder the terms:
29 + 5x = 2(3 + 2x) + -2
29 + 5x = (3 * 2 + 2x * 2) + -2
29 + 5x = (6 + 4x) + -2

Reorder the terms:
29 + 5x = 6 + -2 + 4x

Combine like terms: 6 + -2 = 4
29 + 5x = 4 + 4x

Solving
29 + 5x = 4 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
29 + 5x + -4x = 4 + 4x + -4x

Combine like terms: 5x + -4x = 1x
29 + 1x = 4 + 4x + -4x

Combine like terms: 4x + -4x = 0
29 + 1x = 4 + 0
29 + 1x = 4

Add '-29' to each side of the equation.
29 + -29 + 1x = 4 + -29

Combine like terms: 29 + -29 = 0
0 + 1x = 4 + -29
1x = 4 + -29

Combine like terms: 4 + -29 = -25
1x = -25

Divide each side by '1'.
x = -25

Simplifying
x = -25

See similar equations:

| -9x+-8(5x^2+-5)+6x^2= | | 6x^4y^2-15x^3y^3=0 | | -3(6p+5)-2(4-17p)=3(8+5p) | | 7(3x-4)-7=70 | | .24x-.2=.14x+1-.5x | | 5x-24=-32+9x | | 2x-1y=-34 | | 24x^2+62x+14= | | -9(-4v+4)+-3v+-6= | | (y-2)(y-1)=2(y-2)(y-3) | | 6x^4-20x^3+16x^2= | | 3x-5b=10x | | Y^2-18Y+45=O | | log(7x+6)=2 | | 2a-3=16 | | 42q^2+17qd-15d^2= | | x(x^2-5x-6)=0 | | 10+9(8+5c)= | | f(x)=3x^2-2x+6 | | x+28=25 | | 56v^2+17vb-3b^2= | | 8+2x-4=6+4(x-1) | | 8+2x-4=6+4 | | -5(-9+-10t)+10(3+-5t)= | | 3[x+2(x-7)]=-60 | | 5x+28=35 | | 6-(-5)r=5r-3 | | -9(-1+-4k)+k= | | 2(x+4)=6-1(3x-2)-1 | | Y=log[4](x^2-4x-21) | | x-7=-.25 | | 8x-29=-77+2x |

Equations solver categories